An interface-stable sulfide electrolyte lithium battery and a preparation method thereof

CN122907700APending Publication Date: 2026-10-13JUSHENG ENERGY (JIANGSU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610945977.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0003]然而,硫化物固态电解质在应用于全固态锂电池时,其界面稳定性问题成为制约电池性能的核心瓶颈

Benefits of technology

本发明中的硫化物电解质是以硫银锗矿型电解质Li6PS5Cl为基础,同时掺杂Sn、Si和O元素,不仅解决了传统Li6PS5Cl硫化物电解质界面稳定性差、对空气或水分敏感等缺点,还提高了离子电导率。其中,Sn和Si的共掺杂可以通过“晶格畸变”和“增加锂空位”两种机制共同作用,有望获得比单元素掺杂更高的离子电导率;Si稳定晶体骨架,O钝化表面并提高抗氧化性,两者结合,能同时提升电解质对金属锂负极(抑制还原分解)和高电压正极(抑制氧化分解)的稳定性,并大幅提升空气稳定性,抑制H2S产生。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of lithium batteries, and discloses an interface-stable sulfide electrolyte lithium battery and a preparation method thereof. 1‑x Si 0.5x Sn 0.5x S 5‑x‑ b O b Cl 1+x ; wherein 0.01<=x<=0.03, 0.1<=b<=0.2 is a sulfide electrolyte material. The positive electrode is composed of a positive electrode active material, a conductive agent, the sulfide electrolyte material and a binder, wherein the positive electrode active material is LTMA-coated lithium cobaltate. The sulfide electrolyte lithium battery is compatible with an existing sulfide electrolyte preparation process, and the prepared lithium battery is excellent in electrochemical performance and stable in interface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery technology, specifically to an interface-stable sulfide electrolyte lithium battery and its preparation method. Background Technology

[0002] With the increasing demands for battery energy density and safety performance from electric vehicles and high-end consumer electronics, traditional liquid lithium-ion batteries, due to the flammability, leakage, and limited electrochemical window of organic electrolytes, are no longer sufficient to meet the needs of next-generation high-energy-density energy storage systems. All-solid-state lithium batteries based on inorganic solid-state electrolytes are considered a key technological path to overcome existing energy density bottlenecks due to their inherent safety and compatibility with high-voltage cathodes and lithium metal anodes. Among them, sulfide solid electrolytes (such as the silver-germanium sulfide type Li6PS5Cl and LGPS systems) have become a research hotspot in the field of all-solid-state batteries due to their high ionic conductivity comparable to liquid electrolytes and good mechanical ductility.

[0003] However, when sulfide solid electrolytes are applied to all-solid-state lithium batteries, their interface stability becomes a core bottleneck restricting battery performance. On one hand, sulfide electrolytes are highly sensitive to air and moisture, easily undergoing hydrolysis to generate highly toxic hydrogen sulfide gas, leading to material structure damage and a sharp decrease in ionic conductivity, imposing stringent requirements on their preparation, storage, and battery assembly environments. More critically, there is interfacial chemical and electrochemical incompatibility between sulfide electrolytes and the positive and negative electrode materials: on the positive electrode side, when matched with high-voltage positive electrode materials (such as lithium cobalt oxide and high-nickel ternary materials), the electrochemical window of the sulfide electrolyte is narrow, making it prone to oxidative decomposition under high-voltage charging. Simultaneously, the space charge layer effect and element interdiffusion exist at the interface between the positive electrode material and the electrolyte, resulting in a continuous increase in interfacial impedance and rapid capacity decay. These interface problems severely restrict the cycle life, rate performance, and commercial application of sulfide all-solid-state lithium batteries. Summary of the Invention

[0004] To address the aforementioned technical problems, this invention provides an interface-stable sulfide electrolyte lithium battery and its preparation method.

[0005] The objective of this invention can be achieved through the following technical solutions: An interface-stabilized sulfide electrolyte lithium battery includes a positive electrode, a negative electrode, and a sulfide electrolyte disposed between the positive and negative electrodes; the positive electrode is composed of a positive electrode active material, a conductive agent, a sulfide electrolyte material, and a binder; the negative electrode is a lithium foil; the positive electrode active material is LTMA (Li-Ti-Mg-Al) coated lithium cobalt oxide; The sulfide electrolyte material is Li6P. 1-x Si 0.5xSn 0.5x S 5-x-b O b Cl 1+x Where, 0.01≤x≤0.03, 0.1≤b≤0.2; The sulfide electrolyte material is prepared by the following steps: Step A1: Mix Li2S, P2S5, LiCl, SnS2, SiS2 and P2O5, then grind them to obtain the premix.

[0006] Further, the grinding in step A1 is: grinding in a mortar for 30 minutes.

[0007] Furthermore, Sn doping typically occupies P sites because Sn 4+ The ionic radius is greater than that of P. 5+ This causes local expansion of the crystal lattice, widening the lithium-ion transport channels. Simultaneously, to maintain charge balance, Sn... 4+ Replace P 5+ It introduces additional lithium vacancies, thereby increasing the carrier concentration and significantly improving the intrinsic ionic conductivity of the electrolyte.

[0008] Furthermore, Si is also frequently used to replace P. On the one hand, the bond energy of the Si-S bond is stronger than that of the PS bond. This "anchoring effect" can significantly enhance the stability of the crystal structure and suppress the decomposition of the electrolyte by side reactions during contact with the electrode or during cycling. On the other hand, Si doping also helps to form a more stable passivation layer in situ at the interface, thereby improving the cycle life and critical current density of the battery.

[0009] Furthermore, O typically replaces S in the electrolyte due to its higher electronegativity. Introducing O can broaden the electrolyte's electrochemical window, particularly improving its tolerance to high-voltage cathodes. More importantly, oxygen doping enhances the air stability of sulfides. By forming more stable MO (M=P,Si,Sn) bonds, O can effectively reduce the electrolyte's sensitivity to moisture and significantly reduce the generation of harmful H2S gases upon contact with air.

[0010] Step A2: Transfer the premix to a vacuum ball mill jar for sealing and ball milling. After ball milling, place it in a muffle furnace for annealing and cool to room temperature to obtain the sulfide electrolyte material.

[0011] Furthermore, in step A2, the ball milling speed is 450-550 rpm and the ball milling time is 10-14 h.

[0012] Furthermore, the annealing temperature in step A2 is 500-550℃, and the annealing time is 4-5h.

[0013] The LTMA-coated lithium cobalt oxide is prepared by the following steps: Step B1: Add lithium nitrate (LiNO3), magnesium nitrate hexahydrate (Mg(NO3)2·6H2O), and aluminum nitrate nonahydrate (Al(NO3)3·9H2O) to anhydrous ethanol and mix thoroughly to obtain premix 1; add tetrabutyl titanate to anhydrous ethanol, then add glacial acetic acid and mix thoroughly to obtain premix 2. Further, the molar ratio of Li:Ti:Mg:Al in the reactants described in step B1 is 1-1.2:1:0.1-0.3:0.1-0.3; Furthermore, the amount of glacial acetic acid used in step B1 is approximately 10%-20% of the volume of tetrabutyl titanate; Step B2: Under stirring conditions, premixed solution 2 is slowly added dropwise to premixed solution 1, and then stirring is continued for 30-60 min. Then 1 g of lithium cobalt oxide is added and stirred for 1-2 h. Then the temperature is raised to 50-70℃ and stirred until the solvent is basically evaporated. The mixture is dried, ground, and the precursor mixture is collected. Step B3: Hold the precursor mixture at 300-400℃ for 2 hours, then at 550-700℃ for 4-8 hours, and cool to room temperature to obtain LTMA-coated lithium cobalt oxide. Furthermore, the heating rate in step B3 is 2-5°C / min; Furthermore, the total mass of the LTMA coating layer accounts for 0.5wt%-1.5wt% of the lithium cobalt oxide.

[0014] A method for preparing an interface-stable sulfide electrolyte lithium battery includes the following steps: Step S1: Mix the sulfide electrolyte material, LTMA-coated lithium cobalt oxide and acetylene black, grind them, then mix and stir them evenly with polytetrafluoroethylene, and perform the first pressing to obtain the positive electrode film; perform the second pressing of the sulfide electrolyte material to obtain the sulfide electrolyte. Step S2: Place the positive electrode film on one side of the sulfide electrolyte for the third pressing, and then place the lithium foil on the other side of the sulfide electrolyte for the fourth pressing, thus obtaining an interface-stable sulfide electrolyte lithium battery. Further, the mass ratio of the sulfide electrolyte material, LTMA-coated lithium cobalt oxide, acetylene black, and polytetrafluoroethylene in step S1 is 20-30:60-75:2-5:1-2.5; Further, in step S1, the first compression condition is: compression pressure is 30 MPa, and compression time is 2 min; the second compression condition is: 300 MPa, and compression time is 5 min. Furthermore, the third pressing condition described in step S2 is: pressing pressure of 300 MPa and pressing time of 3 min; the fourth pressing condition is: 70 MPa and pressing time of 3 min.

[0015] The beneficial effects of this invention are: The sulfide electrolyte in this invention is based on the silver sulfide-germanium ore type electrolyte Li6PS5Cl, and is simultaneously doped with Sn, Si, and O elements. This not only solves the shortcomings of traditional Li6PS5Cl sulfide electrolytes, such as poor interfacial stability and sensitivity to air or moisture, but also improves ionic conductivity. Specifically, the co-doping of Sn and Si can work through two mechanisms—"lattice distortion" and "increased lithium vacancies"—and is expected to achieve higher ionic conductivity than single-element doping. Si stabilizes the crystal framework, while O passivates the surface and improves oxidation resistance. The combination of these two factors can simultaneously improve the electrolyte's stability to both the lithium metal anode (suppressing reductive decomposition) and the high-voltage cathode (suppressing oxidative decomposition), and significantly improve air stability, suppressing H2S generation.

[0016] The positive electrode active material in this invention is LTMA-coated lithium cobalt oxide. The LTMA coating layer forms a dense physical barrier on the surface of the lithium cobalt oxide particles, separating the positive electrode active material from the sulfide electrolyte and preventing direct electron exchange between lithium cobalt oxide and sulfides, thereby inhibiting the oxidative decomposition reaction. The introduction of the coating layer not only optimizes the electrode interface structure and reduces interfacial side reactions, but also significantly enhances the rapid migration ability of lithium ions at the electrode-solid electrolyte interface. The composite oxide containing Mg and Al in the coating layer is less prone to cation exchange reactions when in contact with sulfides, thus avoiding interfacial phase transitions and resistance increases. Furthermore, lithium cobalt oxide undergoes anisotropic volume changes during charging and discharging, while the coating layer, with its elastic modulus, can absorb the stress generated by the volume changes. The coating layer formed by the sol-gel method can completely cover the particle surface, avoiding local stress concentration. Compared to the rigid surface of lithium cobalt oxide, the coating layer surface has higher surface energy or better roughness, which is beneficial to the tight adhesion of sulfide electrolyte particles and can improve the solid-solid contact between the sulfide solid electrolyte and the cathode particles. Detailed Implementation

[0017] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0018] The lithium batteries assembled in the following examples were all completed in an argon-protected glove box, and the concentration of water molecules and oxygen in the experimental environment was strictly controlled to be below 0.1 ppm.

[0019] The lithium battery assembled in the following examples uses a positive electrode film of 10 mg, a sulfide electrolyte of 100 mg, a lithium foil thickness of 100 μm and a diameter of 6 mm, and an assembly mold of 10 mm diameter PEEK resin mold liner.

[0020] Example 1: Sulfide electrolyte material (Li6P) 0.99 Si 0.005 Sn 0.005 S 4.89 O 0.1 Cl 1.01 ) Under argon atmosphere, Li₂S, P₂S₅, LiCl, SnS₂, SiS₂, and P₂O₅ in a molar ratio of 2.495:0.475:1.01:0.005:0.005:0.02 were weighed and ground in a mortar for 30 minutes to achieve uniform mixing. The mixture was then transferred to a vacuum ball mill jar and sealed for further processing, and ball-milled at 450 rpm for 10 hours. After ball milling, the mixture was transferred to a muffle furnace and annealed at 500°C for 4 hours. After the reaction was complete, the mixture was cooled to room temperature to obtain the sulfide electrolyte material Li₆P. 0.99 Si 0.005 Sn 0.005 S 4.89 O 0.1 Cl 1.01。

[0021] LTMA-coated lithium cobalt oxide is prepared by the following steps: Step B1: Add LiNO3, Mg(NO3)2·6H2O, and Al(NO3)3·9H2O to anhydrous ethanol and mix thoroughly to obtain premix 1; add tetrabutyl titanate to anhydrous ethanol, then add glacial acetic acid and mix thoroughly to obtain premix 2; the molar ratio of Li:Ti:Mg:Al in the reactants is 1:1:0.1:0.1, and the amount of glacial acetic acid used is approximately 10% of the volume of tetrabutyl titanate. Step B2: Under stirring conditions, premixed solution 2 is slowly added dropwise to premixed solution 1, then stirring is continued for 30 min, then 1 g of lithium cobalt oxide is added and stirred for 1 h, then the temperature is raised to 50 °C and stirred until the solvent is basically evaporated, dried, ground and collected. Step B3: The precursor mixture is kept at 300℃ for 2 hours, then at 550℃ for 4 hours, and cooled to room temperature to obtain LTMA-coated lithium cobalt oxide. The heating rate is 2℃ / min, and the total mass of the LTMA coating layer accounts for 0.5wt% of the lithium cobalt oxide.

[0022] Example 2: Sulfide electrolyte material (Li6P) 0.98 Si 0.01 Sn 0.01 S 4.78 O 0.2 Cl1.02 ) Under argon atmosphere, Li₂S, P₂S₅, LiCl, SnS₂, SiS₂, and P₂O₅ in a molar ratio of 2.49:0.45:1.02:0.01:0.01:0.04 were weighed and ground in a mortar for 30 minutes to achieve uniform mixing. The mixture was then transferred to a vacuum ball mill jar and sealed for further treatment, and ball-milled at 500 rpm for 12 hours. After ball milling, the mixture was transferred to a muffle furnace and annealed at 500°C for 4.5 hours. After the reaction was complete, the mixture was cooled to room temperature to obtain the sulfide electrolyte material Li₆P. 0.98 Si 0.01 Sn 0.01 S 4.78 O 0.2 Cl 1.02。

[0023] LTMA-coated lithium cobalt oxide is prepared by the following steps: Step B1: Add LiNO3, Mg(NO3)2·6H2O, and Al(NO3)3·9H2O to anhydrous ethanol and mix thoroughly to obtain premix 1; add tetrabutyl titanate to anhydrous ethanol, then add glacial acetic acid and mix thoroughly to obtain premix 2; the molar ratio of Li:Ti:Mg:Al in the reactants is 1.1:1:0.2:0.2, and the amount of glacial acetic acid used is approximately 15% of the volume of tetrabutyl titanate. Step B2: Under stirring conditions, premixed solution 2 is slowly added dropwise to premixed solution 1, and then stirring is continued for 45 min. Then 1 g of lithium cobalt oxide is added and stirred for 1.5 h. The temperature is then raised to 60 °C and stirred until the solvent is basically evaporated. The mixture is dried, ground, and the precursor mixture is collected. Step B3: The precursor mixture is kept at 350℃ for 2 hours, then at 650℃ for 6 hours, and cooled to room temperature to obtain LTMA-coated lithium cobalt oxide. The heating rate is 3℃ / min, and the total mass of the LTMA coating layer accounts for 1 wt% of the lithium cobalt oxide.

[0024] Example 3: Sulfide electrolyte material (Li6P) 0.975 Si 0.0125 Sn 0.0125 S 4.875 O 0.1 Cl 1.025 ) Under argon atmosphere, Li₂S, P₂S₅, LiCl, SnS₂, SiS₂, and P₂O₅ in a molar ratio of 2.4875:0.4675:1.025:0.0125:0.0125:0.02 were weighed and ground in a mortar for 30 minutes to achieve uniform mixing. The mixture was then transferred to a vacuum ball mill jar, sealed, and ball-milled at 550 rpm for 14 hours. After ball milling, the mixture was transferred to a muffle furnace and annealed at 550°C for 5 hours. After the reaction was complete, the mixture was cooled to room temperature to obtain the sulfide electrolyte material Li₆P. 0.975 Si 0.0125 Sn 0.0125 S 4.875 O 0.1 Cl 1.025。

[0025] LTMA-coated lithium cobalt oxide is prepared by the following steps: Step B1: Add LiNO3, Mg(NO3)2·6H2O, and Al(NO3)3·9H2O to anhydrous ethanol and mix thoroughly to obtain premix 1; add tetrabutyl titanate to anhydrous ethanol, then add glacial acetic acid and mix thoroughly to obtain premix 2; the molar ratio of Li:Ti:Mg:Al in the reactants is 1.2:1:0.3:0.3, and the amount of glacial acetic acid used is approximately 20% of the volume of tetrabutyl titanate. Step B2: Under stirring conditions, premixed solution 2 is slowly added dropwise to premixed solution 1, and then stirring is continued for 60 min. Then 1 g of lithium cobalt oxide is added and stirred for 2 h. Then the temperature is raised to 70 °C and stirred until the solvent is basically evaporated. The mixture is dried, ground, and the precursor mixture is collected. Step B3: The precursor mixture is kept at 400℃ for 2 hours, then at 700℃ for 8 hours, and cooled to room temperature to obtain LTMA-coated lithium cobalt oxide. The heating rate is 5℃ / min, and the total mass of the LTMA coating layer accounts for 1.5wt% of the lithium cobalt oxide.

[0026] Example 4: A method for preparing an interface-stable sulfide electrolyte lithium battery includes the following steps: Step S1: Mix the sulfide electrolyte material prepared in Example 1, the LTMA-coated lithium cobalt oxide prepared in Example 1, and acetylene black, grind them together, then mix and stir them evenly with polytetrafluoroethylene, and perform a first pressing to obtain a positive electrode film; perform a second pressing of the sulfide electrolyte material to obtain the sulfide electrolyte. Preferably, the mass ratio of the sulfide electrolyte material prepared in Example 1, the LTMA-coated lithium cobalt oxide prepared in Example 1, the acetylene black, and the polytetrafluoroethylene in step S1 is 20:75:3.5:1.5. Preferably, in step S1, the first pressing conditions are: pressing pressure of 30 MPa and pressing time of 2 min; the second pressing conditions are: 300 MPa and pressing time of 5 min. Step S2: Place the positive electrode film on one side of the sulfide electrolyte for the third pressing, and then place the lithium foil on the other side of the sulfide electrolyte for the fourth pressing, thus obtaining an interface-stable sulfide electrolyte lithium battery. Preferably, the third pressing condition in step S2 is: pressing pressure of 300 MPa and pressing time of 3 min; the fourth pressing condition is: 70 MPa and pressing time of 3 min.

[0027] Example 5: A method for preparing an interface-stable sulfide electrolyte lithium battery includes the following steps: Step S1: Mix the sulfide electrolyte material prepared in Example 2, the LTMA-coated lithium cobalt oxide prepared in Example 2, and acetylene black, grind them, then mix and stir them evenly with polytetrafluoroethylene, and perform a first pressing to obtain a positive electrode film; perform a second pressing of the sulfide electrolyte material to obtain the sulfide electrolyte. Preferably, the mass ratio of the sulfide electrolyte material prepared in Example 2 in step S1, the LTMA-coated lithium cobalt oxide prepared in Example 2, the acetylene black, and the polytetrafluoroethylene is 25:70:4:1. Preferably, in step S1, the first pressing conditions are: pressing pressure of 30 MPa and pressing time of 2 min; the second pressing conditions are: 300 MPa and pressing time of 5 min. Step S2: Place the positive electrode film on one side of the sulfide electrolyte for the third pressing, and then place the lithium foil on the other side of the sulfide electrolyte for the fourth pressing, thus obtaining an interface-stable sulfide electrolyte lithium battery. Preferably, the third pressing condition in step S2 is: pressing pressure of 300 MPa and pressing time of 3 min; the fourth pressing condition is: 70 MPa and pressing time of 3 min.

[0028] Example 6: A method for preparing an interface-stable sulfide electrolyte lithium battery includes the following steps: Step S1: Mix the sulfide electrolyte material prepared in Example 3, the LTMA-coated lithium cobalt oxide prepared in Example 3, and acetylene black, grind them, then mix and stir them evenly with polytetrafluoroethylene, and perform a first pressing to obtain a positive electrode film; perform a second pressing of the sulfide electrolyte material to obtain the sulfide electrolyte. Preferably, the mass ratio of the sulfide electrolyte material prepared in Example 3 in step S1, the LTMA-coated lithium cobalt oxide prepared in Example 3, the acetylene black and the polytetrafluoroethylene is 30:65:3:2. Preferably, in step S1, the first pressing conditions are: pressing pressure of 30 MPa and pressing time of 2 min; the second pressing conditions are: 300 MPa and pressing time of 5 min. Step S2: Place the positive electrode film on one side of the sulfide electrolyte for the third pressing, and then place the lithium foil on the other side of the sulfide electrolyte for the fourth pressing, thus obtaining an interface-stable sulfide electrolyte lithium battery. Preferably, the third pressing condition in step S2 is: pressing pressure of 300 MPa and pressing time of 3 min; the fourth pressing condition is: 70 MPa and pressing time of 3 min.

[0029] Comparative Example 1: This comparative example is a sulfide electrolyte lithium battery. The difference from Example 6 is that the sulfide electrolyte material prepared in Example 3 is replaced with a silver-germanium sulfide electrolyte Li6PS5Cl. All other aspects are the same.

[0030] Comparative Example 2: This comparative example is a sulfide electrolyte lithium battery. The difference from Example 6 is that lithium cobalt oxide is used instead of the LTMA-coated lithium cobalt oxide prepared in Example 3. All other aspects are the same.

[0031] Comparative Example 3: This comparative example is a sulfide electrolyte lithium battery. The difference from Example 6 is that the sulfide electrolyte material prepared in Example 3 is replaced by the silver sulfide germanium mineral type electrolyte Li6PS5Cl, and the LTMA-coated lithium cobalt oxide prepared in Example 3 is replaced by lithium cobalt oxide.

[0032] The performance of the sulfide electrolyte lithium batteries prepared in Examples 4-6 and Comparative Examples 1-3 was tested: (1) The air stability of the sulfide electrolyte materials prepared in Examples 1-3 and the silver sulfide germanium ore type electrolyte Li6PS5Cl (comparative example) was tested; Test conditions: The sample was exposed to air at room temperature and 10% humidity. Its air stability was tested by recording the amount of H2S gas produced by the electrolyte. An H2S gas sensor (BH-90A), a 0.5g sulfide electrolyte sample, and a stirring fan were placed in a sealed container to ensure uniform gas distribution. After placing the electrolyte in humid air within the sealed container, the amount of H2S gas produced by the sample was calculated based on the H2S concentration measured by the H2S gas sensor. The test results are shown in Table 1.

[0033] (2) In an argon-filled glove box, 100 mg of sulfide solid electrolyte powder was weighed and placed in a mold battery (Wuhan Chuangneng CN-01) with stainless steel sheets at both ends with a diameter of 9 mm. The battery was then pressurized to 200 MPa, and the electrolyte sheet thickness was 1 mm. The mold battery was used for AC impedance spectroscopy testing. At 25 °C, the electrolyte impedance was determined by electrochemical impedance spectroscopy (EIS). On an electrochemical workstation (ChenHua, CHI630E), the impedance was measured by applying a DC polarization voltage of 1 V with an amplitude of 50 mV and a frequency range of 1 Hz-10 MHz. The ionic conductivity of the electrolyte material was calculated according to the following formula: σ = L / (R·S), where σ is the ionic conductivity in units of S·cm. –1 L is the thickness of the electrolyte sheet, in cm; R is the electrolyte resistance, in Ω; S is the effective contact area between the stainless steel sheet and the electrolyte powder, in cm². 2 The test results are shown in Table 1.

[0034] Table 1: Performance Test Results <![CDATA[Total amount of H2S generated after 60 min (cm 3 / g)]]> 1.56 1.45 1.37 3.86 Ionic conductivity (mS / cm) 9.1 9.5 9.8 4.6 (3) Electrochemical performance test: The lithium batteries prepared in Examples 4-6 and Comparative Examples 1-3 were placed in a special test device and constant current charge-discharge test was performed. The test conditions were charge-discharge voltage range of 2.5-4.2V, charge-discharge rate of 0.1C, 0.5C and 1C, test temperature of 25℃, and capacity retention rate after 100 cycles. The test results are shown in Table 2: Table 2: Performance Test Results

[0035] As can be seen from Tables 1 and 2, the sulfide electrolyte material introduced into the sulfide electrolyte lithium battery of the present invention has excellent ionic conductivity and air stability. The introduction of LTMA-coated lithium cobalt oxide as a positive electrode active material into the lithium battery can improve the interfacial stability between the electrolyte and the positive electrode, thereby enabling the lithium battery to have excellent rate performance and cycle stability.

[0036] The above content is merely an example and illustration of the concept of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the scope defined by the inventive concept, they should all fall within the protection scope of the present invention.

Claims

1. A lithium battery with an interface-stabilized sulfide electrolyte, characterized in that, It includes a positive electrode, a negative electrode, and a sulfide electrolyte disposed between the positive and negative electrodes; the positive electrode is composed of a positive electrode active material, a conductive agent, a sulfide electrolyte material, and a binder; the negative electrode is a lithium foil; the positive electrode active material is LTMA-coated lithium cobalt oxide; The sulfide electrolyte material is Li6P. 1-x Si 0.5x Sn 0.5x S 5-x-b O b Cl 1+x Where 0.01≤x≤0.03, 0.1≤b≤0.

2.

2. The interface-stabilized sulfide electrolyte lithium battery according to claim 1, characterized in that, The sulfide electrolyte material is prepared by the following steps: Step A1: Mix Li2S, P2S5, LiCl, SnS2, SiS2 and P2O5, then grind them to obtain the premix. Step A2: Transfer the premix to a vacuum ball mill jar for sealing and ball milling. After ball milling, place it in a muffle furnace for annealing and cool to room temperature to obtain the sulfide electrolyte material.

3. The interface-stabilized sulfide electrolyte lithium battery according to claim 2, characterized in that, The grinding process described in step A1 involves grinding the food in a mortar for 30 minutes.

4. The interface-stabilized sulfide electrolyte lithium battery according to claim 2, characterized in that, The ball milling speed in step A2 is 450-550 rpm, the ball milling time is 10-14 h, the annealing temperature is 500-550℃, and the annealing time is 4-5 h.

5. The interface-stabilized sulfide electrolyte lithium battery according to claim 1, characterized in that, The LTMA-coated lithium cobalt oxide is prepared by the following steps: Step B1: Add LiNO3, Mg(NO3)2·6H2O and Al(NO3)3·9H2O to anhydrous ethanol and mix well to obtain premix 1; add tetrabutyl titanate to anhydrous ethanol, then add glacial acetic acid and mix well to obtain premix 2. Step B2: Under stirring conditions, premixed solution 2 is slowly added dropwise to premixed solution 1, and then stirring is continued for 30-60 min. Then 1 g of lithium cobalt oxide is added and stirred for 1-2 h. Then the temperature is raised to 50-70℃ and stirred until the solvent is basically evaporated. The mixture is dried, ground, and the precursor mixture is collected. Step B3: Hold the precursor mixture at 300-400℃ for 2 hours, then at 550-700℃ for 4-8 hours, and cool to room temperature to obtain LTMA-coated lithium cobalt oxide.

6. The interface-stabilized sulfide electrolyte lithium battery according to claim 5, characterized in that, In step B1, the molar ratio of Li:Ti:Mg:Al in the reactants is 1-1.2:1:0.1-0.3:0.1-0.3, and the amount of glacial acetic acid used is about 10%-20% of the volume of tetrabutyl titanate.

7. The interface-stabilized sulfide electrolyte lithium battery according to claim 5, characterized in that, The heating rate in step B3 is 2-5℃ / min.

8. The interface-stabilized sulfide electrolyte lithium battery according to claim 5, characterized in that, The total mass of the LTMA coating layer accounts for 0.5wt%-1.5wt% of the lithium cobalt oxide.

9. A method for preparing an interface-stabilized sulfide electrolyte lithium battery according to any one of claims 1-8, characterized in that, Includes the following steps: Step S1: Mix the sulfide electrolyte material, LTMA-coated lithium cobalt oxide and acetylene black, grind them, then mix and stir them evenly with polytetrafluoroethylene, and perform the first pressing to obtain the positive electrode film; perform the second pressing of the sulfide electrolyte material to obtain the sulfide electrolyte. Step S2: Place the positive electrode film on one side of the sulfide electrolyte for the third pressing, and then place the lithium foil on the other side of the sulfide electrolyte for the fourth pressing, thus obtaining an interface-stable sulfide electrolyte lithium battery.

10. The method for preparing an interface-stabilized sulfide electrolyte lithium battery according to claim 9, characterized in that, The mass ratio of the sulfide electrolyte material, LTMA-coated lithium cobalt oxide, acetylene black, and polytetrafluoroethylene in step S1 is 20-30:60-75:2-5:1-2.

5. The first pressing conditions in step S1 are: pressing pressure of 30 MPa and pressing time of 2 min; the second pressing conditions are: 300 MPa and pressing time of 5 min. The third pressing conditions in step S2 are: pressing pressure of 300 MPa and pressing time of 3 min; the fourth pressing conditions are: 70 MPa and pressing time of 3 min.